2022
DOI: 10.5194/tc-16-1941-2022
|View full text |Cite
|
Sign up to set email alerts
|

Flexural and compressive strength of the landfast sea ice in the Prydz Bay, East Antarctic

Abstract: Abstract. A total of 25 flexural and 55 uniaxial compressive strength tests were conducted in laboratory using landfast sea ice samples collected in the Prydz Bay. Three-point bending tests were performed at ice temperatures of −12 to −3 ∘C with force applied vertically to original ice surface, and compressive strength tests were performed at −3 ∘C with a strain-rate level of 10−6–10−2 s−1 in the directions vertical and horizontal to ice surface. Judging from crystal structure, the ice samples were divided int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Therefore, the gas volume should be considered when analyzing the physical factors affecting its mechanical properties, especially for laboratory small-scale ice specimens tested at relatively high ambient temperatures. However, rare studies have quantitatively examined porosity's influence on sea ice flexural strength (Wang et al, 2022). Figure 8B shows the results of flexural strength σ f versus the square root of porosity obtained in this study.…”
Section: Porositymentioning
confidence: 69%
See 2 more Smart Citations
“…Therefore, the gas volume should be considered when analyzing the physical factors affecting its mechanical properties, especially for laboratory small-scale ice specimens tested at relatively high ambient temperatures. However, rare studies have quantitatively examined porosity's influence on sea ice flexural strength (Wang et al, 2022). Figure 8B shows the results of flexural strength σ f versus the square root of porosity obtained in this study.…”
Section: Porositymentioning
confidence: 69%
“…The simple beam tests include three-point and fourpoint bending tests performed in the field or a laboratory, often with small sizes (Ji et al, 2011). Full-scale in-situ tests can provide the actual mechanical properties of the whole natural ice sheets in practical applications, but they are usually highly time-and labor-consuming (Aly et al, 2019;Wang et al, 2022). Small-scale laboratory tests are easier to conduct with accurate testing machines and flexible settings of test conditions (Cox and Weeks, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3b). Detailed description 150 on the machine can be found in Wang et al (2022). The machine is equipped with a force sensor of 100 kN capacity and ±0.5 % accuracy as well as a displacement sensor with ±2 μm accuracy.…”
Section: Uniaxial Compressive Strength Testmentioning
confidence: 99%
“…The sea ice porosity has been adopted to estimate sea ice strain modulus in the engineering standards of ISO19906 (2010), which, however, is replaced by sea ice brine volume fraction in the latest version standard of ISO 19906 (2019). Recent experiments conducted by Wang et al (2022) showed that both brine volume fraction and porosity had no statistically significant effect on sea ice strain modulus. Sea ice substructure is much more important, and the strain modulus increased with increasing platelet spacing.…”
Section: Introductionmentioning
confidence: 97%